Improving Students' Learning Outcomes in Learning English for Special Purposes through The Role-Playing Method - Dwi Handayani Silitonga; Haya Haratikka (English Education Department at FKIP Nommensen University, 2023)
STIE Bina Karya students where their learning focus is not on English, but they have to take English for a Specific Purpose as one of the general subjects. Therefore, delivering English for specific purposes material requires an appropriate learning method. This research aims to describe the application of the Role-Playing Method for STIE Bina Karya students. This Class Action Research applied two cycles. The research subjects are 70 students from the first semester who were chosen randomly. This research used tests, questionnaires, and observations in collecting the data. In analyzing the data, the student's correct answer was divided by the number of items and times 100 to get the score. Research results showed that there is an increase in learning outcomes by applying the role-playing method. In the initial test, student learning outcomes is 35.73. Then in cycle I, it increased to 61.14 and increased again to 77.36 in cycle II. Questionnaire data also proved that the Role-Playing method can not only improve student learning outcomes but can also increase students' non-English study program interest in learning English for specific purposes.